Postpartum hemorrhage and long-term cardiovascular disease risk: a comprehensive systematic review and meta-analysis - Fiqih Faizara Ustadi; Alma Dhiani Paramita; Cinta Adinda Roswinabila; Puguh Oktavian; Manggala Pasca Wardhana (The Journal of Maternal-Fetal & Neonatal Medicine, 2025)
Purpose: Postpartum hemorrhage (PPH) is a major contributor to maternal morbidity and mortality and may have long-term consequences on cardiovascular health. This systematic review and meta-analysis aimed to evaluate the association between PPH and the subsequent risk of cardiovascular disease (CVD) in women.Materials and methods: A comprehensive literature search was conducted across major databases to identify cohort studies assessing cardiovascular outcomes in women with a history of PPH. Data from over 9.7 million participants were pooled using a random-effects model to account for inter-study heterogeneity. The primary outcomes included cardiovascular diseases and thromboembolism events. Subgroup analyses were conducted separately for cardiovascular and thromboembolism outcomes. Sensitivity analyses were conducted to examine the consistency and robustness of the pooled estimates.Results: Women with a history of PPH had a 1.76-fold increased risk of developing cardiovascular disease and 2.10-fold increased risk of thromboembolism. The risk was particularly elevated among those requiring transfusion. Cardiovascular risk was most frequent during the first year postpartum and persisted for up to 15 years, particularly among those with hypertensive disorders of pregnancy. Heterogeneity was substantial for cardiovascular disease outcome (I²=99%) and moderate for thromboembolic outcomes (I²=43%). Sensitivity analyses reduced heterogeneity for cardiovascular disease to 77.1%.Conclusions: PPH is associated with a significantly increased long-term risk of both cardiovascular and thromboembolism disease. These findings highlight the importance of postpartum cardiovascular risk screening and preventive interventions in women with a history of severe PPH. Future research should adopt standardized methodologies and focus on high-burden settings, particularly in low- and middle-income countries.